Activity-Based Approach In Social Workers’ Professional Training - Chuiko, Olena (2021)
Social work education in Ukraine has changed dramatically over the last decades. It has a strong connection with the evolution of social work education as a field of professional practice. Recent changes in Ukrainian social policy, in particular the implementation of professional education requirements, based on the competency-oriented approach, the implementation of professional standards for social workers, the distinction of social work in a separate field of science and the complexity of social practice require the creation of unified training curriculum that corresponds to social needs and practice requirements. Creating a meaningful learning environment and raising awareness of professional objectives would be achievable by applying an activity-oriented approach to the professional education of social workers. This means that knowledge could never be isolated from activity. Activity-oriented educational practices contain the core components of professional activities and concern different aspects of social work. Profession-oriented practice includes general (volunteer activities, research, social project design, organizational and management) and additional (communicative, play and game, teamwork) forms and technologies, which demand from students to accumulate their experience in obtaining the essential forms of professional activities. Professional practice encompasses a set of principles, based on the prioritization of the social work profession, individual activity, participation and reflection, which make possible the development of the student's personal maturity and independence.